2005
DOI: 10.1111/j.1600-6143.2005.00747.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Cytomegalovirus Viral Load in Bronchoalveolar Lavage in Lung Transplant Recipients

Abstract: The utility of cytomegalovirus (CMV) viral load (VL)by quantitative hybrid capture assay (Q-HCA) was investigated in bronchoalveolar lavage (BAL) from lung transplant recipients and compared with BAL cultures and blood VL. Forty-three consecutive BAL samples from 27 lung transplant recipients were analyzed. All samples had shell vial (SV) cultures in addition to Q-HCA. Histopathology was done on all lung tissues, and immunohistochemistry (IHC) in those with positive CMV cultures. Fifteen (56%) lung transplant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
1
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 20 publications
4
67
1
5
Order By: Relevance
“…The amount of light emitted is quantified and is proportional to the amount of DNA in the clinical sample. The clinical application of HCA has been demonstrated in several studies conducted on SOT recipients (141,(167)(168)(169), and these studies suggested the correlation between high viral load and the risk of CMV disease. Few studies have reported lower sensitivities than those of antigenemia and PCR-based assays (165,170).…”
Section: Nat In Sot Recipientsmentioning
confidence: 99%
See 4 more Smart Citations
“…The amount of light emitted is quantified and is proportional to the amount of DNA in the clinical sample. The clinical application of HCA has been demonstrated in several studies conducted on SOT recipients (141,(167)(168)(169), and these studies suggested the correlation between high viral load and the risk of CMV disease. Few studies have reported lower sensitivities than those of antigenemia and PCR-based assays (165,170).…”
Section: Nat In Sot Recipientsmentioning
confidence: 99%
“…There have also been investigations to determine whether the degree of viral load is correlated with respiratory disease (141,146). In a study of 27 lung transplant recipients, CMV loads of Ͼ500,000 copies/ml of BAL fluid were highly correlated with biopsy-proven CMV pneumonitis (141).…”
Section: Nucleic Acid-based Methodsmentioning
confidence: 99%
See 3 more Smart Citations